ANALISA KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA MENGGUNAKAN APLIKASI MODEL PERFORMANCE ASSESMENT KELAS X AKUNTANSI SMK - Gustivani Putri Cahya (MEJ (Mathematics Education Journal), 2017)
mathematics communication is a way to express mathematical ideas, either inoral way or written way toward mathematics problems. The ability of students’mathematics communication is very important although there are only few students who can communicate it nowadays, so that it makes the students’ ability decreased. Students only do plain works that demanded a result but do not or rarely asked the origin or process steps in doing it. In determining the ability of students’ written mathematics communication, a teacher can conduct an assessment. One of the assessments that can be used in mathematics learning is a performance assessment.This research used a qualitative descriptive type with written mathematics communication test. Meanwhile, a written rubric of mathematics communication ability was used for analyzing the data. The research was conducted in SMK Muhammadiyah 3 Singosari with students of class X as research subject. A learning subject that was used in measuring students' mathematics communication ability was a system of linear equations and inequalities. In addition, a written test was used as the instrument of this research. The data of written test will be analyzed descriptively then obtained the following data: the ability of students’ written mathematics communication in all assignments is in good category.